Intellectual property : the lifeblood of your company - Elmslie, Mark; Portman, Simon (Chandos intellectual property series., 2006)
Written by two intellectual property (IP) lawyers, experienced in contentious and non-contentious matters, Intellectual Property deals with different types of intellectual property protection and how to apply for them. It also covers how to cope with the infringement of one's intellectual property or allegations that it infringes someone else's intellectual property. Finally, the book advises on how best to exploit one's intellectual property rights and the sort of commercial agreements that will be entered into as a result. Aimed at business people rather than lawyers. Intellectual Property contains concise, practical, day-to-day advice rather than the study of legal theory or case law. Based on the real experience of the authors and their clientsEasy to understand and uncluttered by legal jargon or complicated footnotesApplicable to a wide range of industries.